Distribution and transfer of trace metals in the Aegean Seawater (Eastern Mediterranean Basin) - VOUTSINOU-TALIADOURI, F.; ZERI, C.; MORIKI, A. (Mediterranean Marine Science, 2000)
Recent measurements of dissolved Cd, Cu, Ni and Mn in 324 water samples of the Aegean Sea fill the gap of missing knowledge in this part of the Eastern Mediterranean and try to identify their main input sources and spreading pathways. The analyses indicate that trace metal concentrations in the North and South Aegean Sea are generally in good agreement with those reported for the Western Mediterranean Sea. In the North Aegean Sea the trace metal distribution patterns differentiate mainly according to the existing water masses. Hence, a strong influence of the Black Sea Water, enriched in trace metals, is clearly recorded for Mn. Concentrations of this metal are one order of magnitude higher in the surface layer than those of the deeper waters. This feature is followed to a lesser degree also by Cd, Cu and Ni. Trace metal concentrations in the South Aegean Sea reveal almost constant values throughout the watercolumn similar to those observed in the North Aegean Sea below the depth of 100 m. Manganese values in the South Aegean Sea are considerably lower comparing with the North Aegean ones, showing relatively enhanced surface values which decrease with depth.